2006
DOI: 10.1007/s00330-006-0370-7
|View full text |Cite
|
Sign up to set email alerts
|

Rotator cuff tears: assessment with MR arthrography in 275 patients with arthroscopic correlation

Abstract: We assessed the diagnostic performance of magnetic resonance (MR) arthrography in the diagnosis of articular-sided partial-thickness and full-thickness rotator cuff tears in a large symptomatic population. MR arthrograms obtained in 275 patients including a study group of 139 patients with rotator cuff tears proved by arthroscopy and a control group of 136 patients with arthroscopically intact rotator cuff tendons were reviewed in random order. MR imaging was performed on a 1.0 T system (Magnetom Expert, Sieme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(98 citation statements)
references
References 31 publications
3
92
0
3
Order By: Relevance
“…Barlak et al [36] recently confirmed the negative impact of HSP on rehabilitation outcome in 114 of 187 consecutive patients with stroke. Moreover, Turner-Stokes and Jackson [45] showed that the presence of HSP is strongly associated with prolonged hospital stay and poor recovery of the arm function [46]. All these data suggest that HSP needs to be correctly diagnosed and treated.…”
Section: Discussionmentioning
confidence: 99%
“…Barlak et al [36] recently confirmed the negative impact of HSP on rehabilitation outcome in 114 of 187 consecutive patients with stroke. Moreover, Turner-Stokes and Jackson [45] showed that the presence of HSP is strongly associated with prolonged hospital stay and poor recovery of the arm function [46]. All these data suggest that HSP needs to be correctly diagnosed and treated.…”
Section: Discussionmentioning
confidence: 99%
“…Note that the tear appeared rather as an added bulge of contrast medium into the supraspinatus tendon on VIBE, whereas the tear is sharper delineated on T1-FS currently widely available and routinely used for MR arthrography. However, a study on the accuracy of MR arthrography to evaluate the rotator cuff using a 1.0-T MR unit was recently published [9]. Moreover, claustrophobic patients (VIBE may especially be useful for these patients) may benefit from being imaged in open MR units, which currently have magnet fields up to 1.0 T instead of 1.5 T. In this study, only axial and coronal planes were used to evaluate the rotator cuff.…”
Section: Discussionmentioning
confidence: 99%
“…A normal rotator cuff was scored as 1, fraying and small partial thickness tears on the articular side of the rotator cuff as 2, large or subtotal partial thickness tears on the articular side of the rotator cuff as 3, full thickness tears of the rotator cuff as 4, and full thickness tears with contrast extension into the acromioclavicular joint (geyser sign) as 5. Differentiation between small and large partial thickness tears was based on tear depth, corresponding to a modification of the Ellman classification [9,10]: a small partial thickness tear was defined as involving one third or less of the thickness of the rotator cuff at that particular location, and a large partial thickness tear as more than one third of the thickness of the rotator cuff. The location of the rotator cuff tears was noted to be in the subscapular, supraspinatus, infraspinatus, or teres minor tendons.…”
Section: Methodsmentioning
confidence: 99%
“…7 If it will affect patient management, MRI arthrography is recommended in the diagnosis of partial thickness tears as it has an overall accuracy of 95% for the most common articular-sided tears. 8 One of the reasons why articular sided partial thickness tears may be better appreciated on MRI arthrography than conventional MRI is that a coapted tear is spread apart by the administration of intraarticular contrast under pressure. (Figures 7a, 7b).…”
Section: Partial Thickness Tearsmentioning
confidence: 99%